A toll-like receptor 9 (rs352140) variant is associated with placental inflammation in newborn infants. (2nd July 2016) - Karody, Vijender; Reese, Shawn; Kumar, Navin; Liedel, Jennifer; Jarzembowski, Jason; Sampath, Venkatesh
Abstract: Objective : Chorioamnionitis contributes to premature birth and associated postnatal morbidity. The genetic basis of altered immune responses underlying placental inflammation (PI) remains understudied. The aim of this study was to evaluate the relationship among TLR signaling pathway polymorphisms and different patterns of PI. Methods : Prospective cohort study in infants involving cord blood collection and placental examination for PI. One hundred and fifty-nine infants enrolled in study out of which 28 were term (eight with PI) and 131 preterm (47 with PI). DNA from blood was genotyped for SNPs in TLR2, 4, 5, 9, NFKBI, NFKBIA, TIRAP, and IRAK1 genes using multiplexed single base extension assay. Results : While there were no differences in BW, GA, gender, race, and SPL among infants with or without PI, there was a higher incidence of PPROM, maternal smoking, drug use, and clinical chorioamnionitis among infants with PI. Out of nine TLR variants, only CT and/or TT genotypes of the TLR9 variant ( rs352140 ) were significantly associated ( p = 0.004) with any PI and maternal pattern of inflammation ( p = 0.012) both by univariate analysis and logistic regression. Conclusions : The presence of a variant T allele in a common SNP ( rs352140 ) in the TLR9 gene whose product recognizes bacterial DNA is associated with increased PI.